Minisci reaction of heteroarenes and unactivated C(sp3)–H alkanes via a photogenerated chlorine radical. Issue 12 (23rd January 2023) - Pan, Zi-Tong; Shen, Li-Miao; Dagnaw, Fentahun Wondu; Zhong, Jian-Ji; Jian, Jing-Xin; Tong, Qing-Xiao
Abstract : Minisci reaction of heteroarenes and unactivated C(sp 3 )–H alkanes via a photogenerated chlorine radical from FeCl3 and seawater. Abstract : Here, an efficient Minisci reaction of heteroarenes and unactivated C(sp 3 )–H alkanes was achieved using an inexpensive FeCl3 as a photocatalyst. The photogenerated chlorine radical contributed to the HAT of C–H and subsequently initiated this reaction. Surprisingly, salt water and even seawater can act as a chlorine radical source, which provided an enlightening idea for future organic synthesis methods.